Mobile application for goal sharing - Liao, Yan (Nanyang Technological University, 2021)
This project report aims to provide a overall presentation of the developing process of making a social goal sharing app: “STICK!”. The app itself is a social goal sharing app where users with similar challenges and short-term goals like quitting smoking, working out regularly, dieting, etc., come together to support each other with right motivation and words. The report contains all the necessary details of app development from front-end flowchart and UI&UX designing, back-end and database building all the way to prototyping and troubling-shooting details and finally publishing process in the Google Play app store. Additionally, some of the study reflection as well as experience gained in the due process will be shown in the final chapter as well.